Evaluation of Antidiabetic and Antioxidant Potential of Hydromethanolic Seed Extract of Datura stramonium Linn (Solanaceae) - Cherie Melaku B; Amare GG (Dove Medical Press, 2020)
Bamlaku Cherie Melaku, Gedefaw Getnet Amare Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Gedefaw Getnet AmareWollo University, Dessie 1145, EthiopiaTel +25 1911737428Email gedefawg39@gmail.comBackground: Nature has gifted a variety of phytochemicals having a potential effect against diabetes mellitus. Datura stramonium has been used as a remedy for the treatment of diabetes mellitus. The study aimed to determine the in vivo antidiabetic potential of hydromethanolic seed extract of the plant.Methods: Dried seeds of Datura stramonium were macerated in hydromethanol. Three doses (100, 200, and 400 mg/kg) of the seed extract were given orally to normoglycemic, glucose-loaded, and Streptozocin-induced diabetic mice. Diphenyl-1-picrylhydrazine (DPPH) assay was employed to determine antioxidant activity of the seed extract.Results: All doses of hydromethanolic seed extract of D. stramonium were devoid of any significant hypoglycemic effect in normoglycemic mice compared to the negative control group. Acute glucose reduction was significant (P< 0.05 at 100, P< 0.01 at 200 and 400 mg/kg) with respect to negative control in oral glucose-loaded mice. All doses of seed extract significantly (P< 0.0l) reduced blood glucose level on weeks 1 and 2 in STZ-induced daily-treated diabetic mice. The seed extract at the doses of 200 and 400 mg/kg significantly (P< 0.05) improved the body weight of diabetic mice on weeks 1 and 2. A low (100 mg/kg) dose of the seed extract delayed and significantly (P< 0.05) increased body weight of mice on week 2 compared to negative control. The finding showed that the antioxidant activity of the hydromethanolic seed extract was concentration dependent and comparable with ascorbic acid. IC50 of the seed extract and ascorbic acid was found to be 11.95 and 5.07 mg/mL, respectively.Conclusion: The findings of the study showed that hydromethanolic seed extract of Datura stramonium endowed significant antihyperglycemic and antioxidant activity.Keywords: diabetes, Streptozotocin, Datura stramonium, antioxidant, mice